Weighted RAFT: An Improved Blockchain Consensus Mechanism for Internet of Things Application - Xu, Xiaojun; Hou, Lu; Li, Yankai; Geng, Yunxin (2021 7th International Conference on Computer and Communications (ICCC), 2021)
The integration of blockchain technology and RAFT consensus algorithm could address many of the IoT application security and privacy issues. However, each node in RAFT consensus has equivalent probability of being elected as a leader, which takes no consideration on the communication and computing status of the node. Therefore, in this paper, we propose a weighted RAFT consensus algorithm for IoT applications, which allows IoT gateway with better capacity to have a higher possibility of being elected as the leader compared to the normal RAFT mechanism. Thus, the latency of uploading IoT data on blockchain can be reduced a lot. Simulation results show that the weighted RAFT can reduce the system forwarding latency by 24% at most.